2014
DOI: 10.1371/journal.pone.0091188
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Breeding Population of Adélie Penguins in the Ross Sea, 1981–2012: A Coincidence of Climate and Resource Extraction Effects

Abstract: Measurements of the size of Adélie penguin (Pygoscelis adeliae) colonies of the southern Ross Sea are among the longest biologic time series in the Antarctic. We present an assessment of recent annual variation and trends in abundance and growth rates of these colonies, adding to the published record not updated for more than two decades. High angle oblique aerial photographic surveys of colonies were acquired and penguins counted for the breeding seasons 1981–2012. In the last four years the numbers of Adélie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 44 publications
3
102
1
Order By: Relevance
“…The three penguin habitats on Ross Island are all less than 50 miles from McMurdo Station ( Figure S2) 30 (Lyver et al, 2014) . Penguin activities have been linked previously to particle formation (Weber et al, 1998) , enriching aerosols with oxalate (Legrand et al, 2012) and containing CNHO fragments (Schmale et al, 2013) .…”
Section: Organic Mass and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three penguin habitats on Ross Island are all less than 50 miles from McMurdo Station ( Figure S2) 30 (Lyver et al, 2014) . Penguin activities have been linked previously to particle formation (Weber et al, 1998) , enriching aerosols with oxalate (Legrand et al, 2012) and containing CNHO fragments (Schmale et al, 2013) .…”
Section: Organic Mass and Compositionmentioning
confidence: 99%
“…Penguin activities have been linked previously to particle formation (Weber et al, 1998) , enriching aerosols with oxalate (Legrand et al, 2012) and containing CNHO fragments (Schmale et al, 2013) . Since McMurdo Station is most frequently downwind from Cape Crozier, its estimated ~300,000 penguins are a likely source of this organic and ammonium contribution to particles (Lyver et al, 2014) .…”
Section: Organic Mass and Compositionmentioning
confidence: 99%
“…Recently, satellite measurements have led to a new estimate that suggests an increase in the total number of Adélie penguins, as well as in the number of colonies across the continent (Lynch and LaRue, 2014). Using this technique and ground-based surveys, Adélie populations have been shown to be generally in decline in the Antarctic Peninsula, while other populations are stable or slightly increasing (Cimino et al, 2013;Lyver et al, 2014;Southwell et al, 2015). The use of satellite counts has contributed to the downgrading of the species on the IUCN scale from "Near Threatened" to "Least Concerned" in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Adélie penguin populations in the southern Ross Sea have been increasing (0.067 annual growth rate, 2001-2012), though numbers remain lower than they were in early 1980s [81]. In contrast, emperor penguins have been in decline, with a 50% drop in numbers since the 1970s [71,82].…”
Section: Population and Evolutionary Ecologymentioning
confidence: 99%
“…One explanation for the decline in emperor penguins is a warming event that occurred in the southern Indian Ocean during the 1970s and that reduced sea ice extent [71,82]. A comparison of the Terre Adélie colony with another declining colony at Haswell Island (66°32′S, 93°0 7′E), revealed that numbers of breeding male emperor penguins correlated similarly to sea ice extent in both colonies, suggesting climate fluctuations as a main cause of population changes in the species ( [83]; but see [73,81]). Decreasing sea ice cover seems to be correlated with population declines in both species.…”
Section: Population and Evolutionary Ecologymentioning
confidence: 99%